(untitled) (Journal of Asian Development Studies, 2025)
The study aimed to explore the determinants of initial public offering (IPO) pricing by evaluating the causal relationship between IPO pricing and various firm-related factors, including pre-IPO retention of ownership, age of the firm, firm size, offer size, and investor sentiments. To highlight the impact of factors on investing, data from 93 firms that became publicly listed on the Pakistan Stock Exchange between 2012 and 2017 were collected, using descriptive statistics, correlation, and multiple regression tests. The analysis results showed a mixed effect on IPO pricing. Offer size and pre-IPO retained ownership have a negative impact, while the age of the firm, firm size, and investor sentiments have a positive impact on IPO pricing. Among all the variables, only investor sentiment has a nearly significant value. Later, the model was re-specified through the redundancy process, which asserted that only the size of the firm and the offer size of the IPO have significantly positive and negative effects on IPO pricing, respectively. The mentioned results were specific to the Pakistani stock market, which is an emerging market and considered a volatile market among its counterparts. This research promotes awareness about the factors typically considered and advertised by the IPO firm and investors to inform their decision about investing in the firm going public.